Arsenite induces DNA damage via mitochondrial ROS and induction of mitochondrial permeability transition. (13th July 2017) - Guidarelli, Andrea; Fiorani, Mara; Cerioni, Liana; Scotti, Maddalena; Cantoni, Orazio
Abstract: Arsenite is an established DNA‐damaging agent and human carcinogen. We initially selected conditions in which the metalloid causes DNA strand scission in the absence of detectable apoptotic DNA degradation in U937 cells. This response was suppressed by catalase and by treatments (rotenone and ascorbic acid), or manipulations (respiration‐deficient phenotype), preventing the mitochondrial formation of O 2 − . ( mitoO 2 − . ). MitoO 2 − ., and its dismutation product, H2 O2, are therefore critically involved in the arsenite‐dependent DNA‐damaging response. We then established a link between mitoO 2 − . /H2 O2 and mitochondrial permeability transition (MPT), and found that this second event also promoted the formation of DNA‐damaging species. As a consequence, the DNA damage induced by arsenite, in addition to being abolished by the aforementioned treatments/manipulations, was also significantly reduced by the MPT inhibitor cyclosporin A (CsA). A CsA‐sensitive induction of p53 mRNA expression was also detected. Finally, evidence of CsA‐sensitive DNA strand scission was also obtained in MCF‐7, HT22, and NCTC‐2544 cells. MitoO 2 − . /H2 O2 therefore directly mediates DNA damage induced by arsenite and indirectly promotes the formation of additional DNA‐damaging species via the induction of MPT. © 2017 BioFactors, 43(5):673–684, 2017